Exploring the In Vivo Existence Forms (23 Original Constituents and 147 Metabolites) of Astragali Radix Total Flavonoids and Their Distributions in Rats Using HPLC-DAD-ESI-IT-TOF-MSn - Li-Jia Liu; Hong-Fu Li; Feng Xu; Hong-Yan Wang; Yi-Fan Zhang; Guang-Xue Liu; Ming-Ying Shang; Xuan Wang; Shao-Qing Cai (Molecules, 2020)
Astragali Radix total flavonoids (ARTF) is one of the main bioactive components of Astragali Radix (AR), and has many pharmacological effects. However, its metabolism and effective forms remains unclear. The HPLC-DAD-ESI-IT-TOF-MSn technique was used to screen and tentatively identify the in vivo original constituents and metabolites of ARTF and to clarify their distribution in rats after oral administration. In addition, modern chromatographic methods were used to isolate the main metabolites from rat urine and NMR spectroscopy was used to elucidate their structures. As a result, 170 compounds (23 original constituents and 147 metabolites) were tentatively identified as forms existing in vivo, 13 of which have the same pharmacological effect with ARTF. Among 170 compounds, three were newly detected original constituents in vivo and 89 were new metabolites of ARTF, from which 12 metabolites were regarded as new compounds. Nineteen original constituents and 65 metabolites were detected in 10 organs. Four metabolites were isolated and identified from rat urine, including a new compound (calycoisn-3’-O-glucuronide methyl ester), a firstly-isolated metabolite (astraisoflavan-7-O-glucoside-2’-O-glucuronide), and two known metabolites (daidzein-7-O-sulfate and calycosin-3’-O-glucuronide). The original constituents and metabolites existing in vivo may be material basis for ARTF efficacy, and these findings are helpful for further clarifying the effective forms of ARTF.